At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer: k(8z - 2)=448z^2-224z+35
z(q^2)=-10q^4 - 5
Step-by-step explanation:
k(z) = 7z^2 + 7
k(8z - 2)=7(8z - 2)^2 + 7
k(8z - 2)=7(8z - 2)(8z - 2) + 7
k(8z - 2)=7(64z^2-16z-16z+4) + 7
k(8z - 2)=7(64z^2-32z+4) + 7
k(8z - 2)=7(64z^2-32z+4+1) ==> 7*1=7, so +1 is added in parentheses while +7 is removed outside of parentheses.
k(8z - 2)=7(64z^2-32z+5)
k(8z - 2)=448z^2-224z+35
z(q) = -10q^2 - 5
z(q^2)=-10(q^2)^2 - 5
z(q^2)=-10(q^(2*2)) - 5
z(q^2)=-10q^4 - 5
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.